KRITERIA 29: CARA PANDANG BARU DALAM PENYUSUNAN KALENDER HIJRIYAH - Hendro Setyanto; Fahmi Fatwa Rosyadi Satria Hamdani (Al-Ahkam, 2015)
Hilāl is an early marker of the beginning of the Hijriyah/Qamariyah. The existence of the new moon was used as a reference in the preparation of a system of Islamic calendar. The issue of the new moon it is still be an interesting thing to be studied. In fact there is a lot of research and discussion related with hilāl issues. However, it still has not found an appropriate formula to be used as a reference in creating a standardized system of the Islamic calendar. Currently, there are several criteria that offered to make the calendar system. In this paper, will be presented criteria and other perspectives in formulating a Hijriyah calendar, called the Criteria 29. Some examples of simple calculations and discussions in determining the first day of month of the Hijriyah presented briefly. This elaboration of “Criteria 29” hopefully can give an idea and different viewpoints in order to develop Hijriyah calendar.